Transient Lesion of the Splenium of the Corpus Callosum after Acute Ischemic Stroke - Yamaguchi, Yoshitaka (Intern Med, 2018)
Two patients who showed transient lesions in the splenium of the corpus callosum (SCC) secondary to acute ischemic stroke are reported. Both patients had embolic strokes and showed an isolated lesion in the SCC on magnetic resonance imaging (MRI) 1-2 weeks after the onset of stroke, with a hyperintense lesion on diffusion-weighted imaging and decreased apparent diffusion coefficient values, with no symptoms related to the lesion. In both cases, the lesion disappeared on MRI approximately 1 week later. Clinicians should note that transient SCC lesions can occur following acute ischemic stroke and avoid misdiagnosing them and performing unnecessary examinations or treatment.